APLIKASI E-MARKET SECARA ONLINE DENGAN MENGGUNAKAN CODE IGNITER DAN BARCODE - Muhammad Abrar; Yuswardi Yuswardi (Jurnal Real Riset, 2023)
Nowadays, of course, friends are no longer strangers to Barcodes. Almost on every product packaging sold in shops and supermarkets, be it bread, masks, mineral water, to snacks, a box is printed consisting of thick and thin vertical lines. This is what is called a barcode, and is usually printed neatly in one corner of the product packaging. The goal is to design a payment application between sellers and buyers in supermarkets that is able to handle work in data management. The second is running a payment application as a solution for handling databases with accurate results and not easy to make mistakes in handling payments.Keywords : Barcode , code igniter